2017
DOI: 10.1016/j.cell.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Evolution of Autoreactive Germinal Centers

Abstract: SUMMARY Germinal centers (GCs) are the primary sites of clonal B cell expansion and affinity maturation, directing the production of high-affinity antibodies. This response is a central driver of pathogenesis in autoimmune diseases, such as systemic lupus erythematosus (SLE), but the natural history of autoreactive GCs remains unclear. Here, we present a novel mouse model where the presence of a single autoreactive B cell clone drives the TLR7-dependent activation, expansion, and differentiation of other autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
167
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(187 citation statements)
references
References 42 publications
19
167
1
Order By: Relevance
“…In full agreement, we found that, in contrast to WT controls, GCs can hardly be detected in IgD‐deficient mice at days 4 and 7 of immunization (Fig D and E). On day 10 after immunization, the GC cells in IgD‐deficient mice were mostly localized in multiple small aggregations as compared to the compact GC structures observed in WT mice (Fig E and F; Sander et al , ; Degn et al , ; Inoue et al , ). Moreover, sera from TNP‐Ova‐immunized IgD‐deficient mice contained less TNP‐specific IgG compared to sera from immunized WT mice (Fig G).…”
Section: Resultsmentioning
confidence: 91%
“…In full agreement, we found that, in contrast to WT controls, GCs can hardly be detected in IgD‐deficient mice at days 4 and 7 of immunization (Fig D and E). On day 10 after immunization, the GC cells in IgD‐deficient mice were mostly localized in multiple small aggregations as compared to the compact GC structures observed in WT mice (Fig E and F; Sander et al , ; Degn et al , ; Inoue et al , ). Moreover, sera from TNP‐Ova‐immunized IgD‐deficient mice contained less TNP‐specific IgG compared to sera from immunized WT mice (Fig G).…”
Section: Resultsmentioning
confidence: 91%
“…A non-mutually exclusive alternative model would implicate a generalized process of naïve B-cell activation in SLE and stochastic acquisition of pathogenic autoreactivity through SHM and selection by self-antigen within the GC, an environment specialized in prolonged antigen presentation and cyclical clonal expansion which is rich in self-antigens in part due to high levels of apoptosis and defective apoptotic cell clearance. Another possibility, described in the mouse anti-DNA response (19, 20), is that after being first stimulated by a triggering antigen, autoreactive B cells would subsequently acquire a separate autoreactivity against a different self-antigen (target antigen), through SHM either in the GC (21) or in the local environment of target tissues such as the kidney in patients with lupus nephritis (22). Indeed, this process could also help explain the well-documented phenomenon of epitope spreading responsible for the progressive addition of antigenic targets leading to disease development and progression (23).…”
Section: B-cell and Antibody Repertoires In Slementioning
confidence: 99%
“…47 Perhaps a more ubiquitous feature of the disease is the presence of robust extrafollicular (EF) pathways, a pathogenic mechanism well documented in murine lupus and more recently in human SLE. 47 Perhaps a more ubiquitous feature of the disease is the presence of robust extrafollicular (EF) pathways, a pathogenic mechanism well documented in murine lupus and more recently in human SLE.…”
Section: G Erminal Center Checkp Oints and Toler An Ce Enforcement mentioning
confidence: 99%